Penilaian Kinerja Keuangan Berdasarkan Rasio Arus Kas - Isna Ardila (Ali Institute of Research and Publication, 2026)
This study aims to analyze the cash flow performance of PT Unilever Tbk for the 2020-2024 period through cash flow ratios. A Quantitative descriptive method was chosen as the method in this study. PT Unilever Tbk as the object of research and the subject of research is the financial statements of PT Unilever Tbk for the 2020-2024 period. The data taken from the financial statements are secondary data, namely the income statement, statement of financial position, and cash flow statement. The data analysis technique in this study is by calculating the ratio of operating cash flow to current liabilities, cash-based interest coverage ratio, operating cash flow to total debt ratio, operating cash flow to net income ratio, and capital expenditure coverage ratio. The results of the study indicate that cash from operating activities is not yet fully strong enough to meet short-term obligations and tends to weaken at the end of the period, so that the potential for liquidity risk increases. On the other hand, the company’s ability to pay interest from operating cash flows was very strong, and net income continued to be supported by operating cash flows despite a decline at the end of the period. The company was also able to finance capital expenditures from operating cash flows; however, the long-term decline in capital expenditures should be monitored as it may affect asset renewal and future efficiency. Overall, the company remains strong in terms of interest-paying capacity and cash-based earnings quality, but it needs to strengthen operating cash flows and manage liabilities to keep liquidity pressures under control. Keywords: Financial Performance, Operating Cash Flow, Ratio